Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.11646/phytotaxa.343.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of Microlicia (Melastomataceae) from the Septentrional Espinhaço, Bahia, Brazil

Abstract: The Serra Geral in Licínio de Almeida municipality, Bahia, Brazil, is a transitional area between the “Cerrado” and “Caatinga” domains constituting an ecological corridor that links the northern and southern portions of the Espinhaço Range. The taxonomic treatment of Melastomataceae in this area revealed two new species of Microlicia. Descriptions of the species are provided, including detailed illustrations, and statements of geographical distribution, habitat and IUCN conservation status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Estadual de Maringá, Maringá, Paraná, Brazil. Woodgyer and Zappi 2005, Almeda and Martins 2012, Pataro et al 2013, Jesus et al 2018, 2020a, b, 2022b, Romero and Woodgyer 2018, Gali et al 2022. Within Lavoisiereae, species of Microlicia are recognized by their perennial woody habit associated with diplostemonous, mostly heteranthous flowers, elongate to somewhat reniform seeds with a reticulate-foveolate testa, and a base chromosome number of x = 12 (Versiane et al 2021, Pacifico andAlmeda 2022a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estadual de Maringá, Maringá, Paraná, Brazil. Woodgyer and Zappi 2005, Almeda and Martins 2012, Pataro et al 2013, Jesus et al 2018, 2020a, b, 2022b, Romero and Woodgyer 2018, Gali et al 2022. Within Lavoisiereae, species of Microlicia are recognized by their perennial woody habit associated with diplostemonous, mostly heteranthous flowers, elongate to somewhat reniform seeds with a reticulate-foveolate testa, and a base chromosome number of x = 12 (Versiane et al 2021, Pacifico andAlmeda 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…dates from the 19th century (Cogniaux 1891). During the last three decades, studies on the Bahian species of the genus have mostly been limited to species checklists (Zappi et al 2003, Santos and Silva 2005), an identification key (Woodgyer 2005), regional taxonomic treatments (Woodgyer and Lughadha 1995, Pataro et al 2017) and descriptions of new taxa (Wurdack 1995, Woodgyer and Zappi 2005, 2009, Almeda and Martins 2012, Pataro et al 2013, Jesus et al 2018, Pacifico and Almeda 2018, 2020a, b2020b, 2022b, Romero and Woodgyer 2018, Gali et al 2022). Within Lavoisiereae, species of Microlicia are recognized by their perennial woody habit associated with diplostemonous, mostly heteranthous flowers, elongate to somewhat reniform seeds with a reticulate–foveolate testa, and a base chromosome number of x = 12 (Versiane et al 2021, Pacifico and Almeda 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…The SGLA is an ecotone between the Cerrado and Caatinga biomes with savannic and forest formations (Campos et al 2017). This constitutes an ecological corridor connecting the southern and northern sectors of Espinhaço Range (Silva et al 2008;Zappi 2008) where 24 new occurrences were recorded for the state of Bahia (Campos et al 2017), and already revealed two new endemic species of Microlicia D.Don (Jesus et al 2018). Thus, aiming to collaborate in increasing knowledge about the family Melastomataceae in the state of Bahia, northeast region of Brazil, we present the first record of the genus Fritzschia, coming from SGLA.…”
Section: Introductionmentioning
confidence: 99%